CRISPR/Cas9—The ultimate weapon to battle infectious diseases?. (6th December 2016) - Doerflinger, M.; Forsyth, W.; Ebert, G.; Pellegrini, M.; Herold, M.J.
Abstract: Infectious diseases are a leading cause of death worldwide. Novel therapeutics are urgently required to treat multidrug‐resistant organisms such as Mycobacterium tuberculosis and to mitigate morbidity and mortality caused by acute infections such as malaria and dengue fever virus as well as chronic infections such as human immunodeficiency virus‐1 and hepatitis B virus. The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) system, which has revolutionized biomedical research, holds great promise for the identification and validation of novel drug targets. Since its discovery as an adaptive immune system in prokaryotes, the CRISPR/Cas9 system has been developed into a multi‐faceted genetic modification tool, which can now be used to induce gene deletions or specific gene insertions, such as conditional alleles or endogenous reporters in virtually any organism. The generation of CRISPR/Cas9 libraries that can be used to perform phenotypic whole genome screens provides an important new tool that will aid in the identification of critical host factors involved in the pathogenesis of infectious diseases. In this review, we will discuss the development and recent applications of the CRISPR/Cas9 system used to identify novel regulators, which might become important in the fight against infectious diseases.